2023
DOI: 10.3390/polysaccharides4030017
|View full text |Cite
|
Sign up to set email alerts
|

Lactic Acid Fermentation of Carrageenan Hydrolysates from the Macroalga Kappaphycus alvarezii: Evaluating Different Bioreactor Operation Modes

Adam Tabacof,
Verônica Calado,
Nei Pereira

Abstract: Lactic acid is a molecule used abundantly in the food, cosmetic, and pharmaceutical industries. It is also the building block for polylactic acid, a biodegradable polymer which has gained interest over the last decade. Seaweeds are fast growing, environmentally friendly, and economically beneficial. The Rhodophyta, Kappaphycus alvarezii, is a carrageenan-rich alga, which can be successfully fermented into lactic acid using lactic acid bacteria. Lactobacillus pentosus is a versatile and robust bacterium and an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…Using similar conditions with an even higher biomass concentration of 50% (w/v) mix, Hargreaves et al [22] reached a galactose concentration of 82 g/L. The work carried out by Hargreaves et al [22] and Tabacof et al [24,73] showed that exposing K. alvarezii biomass to prolonged acid hydrolysis results in the formation of 1 g/L of HMF for every 4 g/L of galactose.…”
Section: Processing K Alvarezii Biomass For Fermentation Processesmentioning
confidence: 94%
See 3 more Smart Citations
“…Using similar conditions with an even higher biomass concentration of 50% (w/v) mix, Hargreaves et al [22] reached a galactose concentration of 82 g/L. The work carried out by Hargreaves et al [22] and Tabacof et al [24,73] showed that exposing K. alvarezii biomass to prolonged acid hydrolysis results in the formation of 1 g/L of HMF for every 4 g/L of galactose.…”
Section: Processing K Alvarezii Biomass For Fermentation Processesmentioning
confidence: 94%
“…Hargreaves et al [22] determined that fine powdered charcoal is preferable to charcoal granules, and that approximately 1 g/L of charcoal should be used for each 1 g/L of HMF removed from the hydrolysate. Activated charcoal can also be regenerated via oxidation processes [79], desorption and decomposition methods [80], and thermal treatment [73,81]. Since HMF is a valuable chemical compound [29], its recuperation from the activated charcoal should be considered.…”
Section: Enabling Dilute-acid Hydrolysate Fermentationmentioning
confidence: 99%
See 2 more Smart Citations